Effectiveness of Playing Picture Cards on Language Development in Preschool Children (4-5 Years) - Vianita , Imelda Liena (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
The ability to speak is one of the ability that must be owned by all children aged 4-5 years. Playing with learning is the stimulus the most effective to enhance the language development. One of game in accordance is a game of the picture. The purpose of this study is to know the effectiveness of playing picture cards to the language development in preschoolers (4-5 years). The methode of this research is Pre-Eksperimental Design using One Group Pra-Post Tes Design with sample of 39 respondents. The sampling technique by purposive sampling using statistical tests "Wilcoxon". A data carried out using the DDST test only on the language development sector before and after intervention. The result of the research show language development before being given the intervention by 32 children experiencing delay. Meanwhile after given the intervention, 12 children increased. The result of the test statistic showed p value = 0,001 (0,001 < 0,05). There is the effectiveness of playing picture cards to the language development in preschoolers (4-5 years). The conclusion in this study that playing picture cards effectively improves language development. Providing appropriate and consistent make language development can be growing optimally.